(untitled) (Research, Society and Development, 2021)
Medicinal plants are one of the first forms of medicine known to mankind through teas, and nowadays they are still used as a way to promote health and well-being. Despite being part of government programs, medicinal plants and herbal medicines are still not often indicated. Given this reality, we sought to identify the use of medicinal plants as a factor in health promotion, performing an integrative review, including the PUBMED, LILACS and SCOPUS databases. The descriptors “Medical Plants and Health Promotion” were used to select articles published from 2001 to 2021. Twenty-two articles were selected for analysis. Knowledge about the use of medicinal plants is passed from generation to generation in the family environment, and studies show that there is still a barrier between academic knowledge and popular knowledge, evidenced by research dealing with the view of professionals on encouraging their use the same. There is a trend in the improvement of patients with the use of medicinal plants regarding the aspect of quality of life and well-being, with conversation circles and therapeutic gardens being the main forms of integration between health promotion and medicinal plants and the best ways of decreasing this distance of knowledge.